Body Image and Quality-of-Life in Untreated Versus Brace-Treated Females With Adolescent Idiopathic Scoliosis. Issue 4 (February 2016) - Schwieger, Traci; Campo, Shelly; Weinstein, Stuart L.; Dolan, Lori A.; Ashida, Sato; Steuber, Keli R.
Abstract : Study Design: The Bracing in Adolescent Idiopathic Scoliosis Trial (BrAIST) included skeletally immature high-risk patients with adolescent idiopathic scoliosis (AIS) with moderate curve sizes (20°– 40°). BrAIST was a multicenter, controlled trial using both randomized and preference treatment arms into either an observation group or a brace treatment group. Objective: The aim of this study was to analyze and compare body image and quality-of-life (QOL) in female AIS patients who were observed or treated with a brace. Summary of Background Data: Brace treatment is an effective means for controlling progressive scoliosis and preventing the need for surgery, but there is no consensus regarding the effect of brace treatment on body image or on QOL in adolescents with AIS. Methods: Data from female BrAIST patients in the randomized (n = 132) or preference (n = 187) arms and were observed (n = 120) or brace treated (n = 199) were analyzed. Patients completed the Spinal Appearance Questionnaire (SAQ) and the Pediatric Quality of Life Inventory (PedsQOL) 4.0 Generic Scales at baseline and 6 month follow-up visits up to 2 years. Items on the SAQ measured three body image constructs (self, ideal, and overall). The PedsQOL measured health, activities, feelings, social factors, and school. Results: . In general, there were no significant differences within or between study arms or treatments regarding body image or QOL through 2 years of follow-up. Poorer body image was significantly correlated with poorer QOL during the first 2 years of follow-up regardless of study arm or treatment. Patients who crossed-over to a different treatment and patients with largest Cobb angles ≥ 40 degrees had significantly poorer body image, in particular self-body image, compared with those that did not. Conclusion: This study does not support findings from previous research indicating that wearing a brace has a negative impact on or is negatively impacted by body image or QOL. Level of Evidence: 2